CYTOTOXIC ACTIVITY OF PALLADIUM (II) COMPLEXES OF (1E,6E)-1,7-BIS(4-(DIMETHYLAMINO)PHENYL)HEPTA-1,6-DIENE-3,5-DIONE AGAINST HUMAN COLON CARCINOMA - MIKLÁŠOVÁ, Natalia; MIKLÁŠ, Roman; VIRAG, Piroska; TATOMIR, Corina Bianca; SZALONTAI, Cristina; CENARIU, Diana; DEVÍNSKY, Ferdinand; FISCHER-FODOR, Eva (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Two palladium(II) complexes of (1E,6E)-1,7-bis(4-(dimethilamino) phenyl)hepta-1,6-diene-3,5-dione were synthesized and structurally characterized with the aim of testing their cytotoxicity towards human colon tumor cells in vitro. Complexes A and B have the capacity to inhibit the cell growth in HT-29 and DLD-1 cell lines, the activity of A being superior as a result of a better accumulation inside the tumor cells.